The Effect of Financial Performance Indicators on Stock Prices of Energy Companies Listed on the Indonesia Stock Exchange - Septia Eka Putri; Esi Fitriani Komara (Economic and Business Horizon, 2026)
Stock prices serve as an important indicator of corporate performance and investor confidence in the capital market. However, stock price movements in Indonesia’s energy sector during the 2021–2024 period exhibited considerable volatility, suggesting that variations in companies’ financial performance may influence investor valuation and market prices. This study analyzes the effect of return on assets, return on equity, net profit margin, and debt-to-equity ratio on stock prices of energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. A quantitative explanatory approach was employed using secondary data from 30 purposively selected companies, yielding 120 observations. Panel data regression was conducted using EViews 14. The findings reveal that return on assets, return on equity, net profit margin, and debt-to-equity ratio do not individually have a significant effect on stock prices. However, these variables jointly exert a significant influence. The coefficient of determination (10.54%) indicates that financial performance explains a limited proportion of stock price variation, while 89.46% is attributable to factors outside the model. These findings suggest that stock prices in the energy sector are shaped not only by financial performance but also by external factors, including macroeconomic conditions, commodity price fluctuations, and market sentiment.